Regional dissemination of a trimethoprim-resistance gene cassette via a successful transposable element. - Labar, A.S.; Millman, J.S.; Ruebush, E.; Opintan, J.A.; Bishar, R.A.; Aboderin, A.O.; Okeke, I.N. (PLoS ONE, 2012)
Background: Antimicrobial resistance is a growing international problem. We observed a 50% increase in the prevalence of trimethoprim resistance among fecal Escherichia coli from healthy Nigerian students between 1998 and 2005, a trend to increase that continued in 2009. Methods and Findings: A PCR-based screen revealed that 131 (43.1%) of isolates obtained in Nigeria in 2005 and 2009 carried integron-borne dfrA cassettes. In the case of 67 (51.1%) of these isolates, the cassette was a class 1-integron-borne dfrA7 gene, which has been reported at high prevalence from E. coli isolates from other parts of Africa. Complete sequencing of a 27 Kb dfrA7-bearing plasmid from one isolate located the dfrA7 gene within a Tn21-type transposon. The transposon also contained an IS26-derived bla/sul/str element, encoding resistance to b-lactams, sulphonamides and streptomycin, and mercury resistance genes. Although the plasmid backbone was only found in 12 (5.8%) of trimethoprim resistant isolates, dfrA7 and other transposon-borne genes were detected in 14 (16.3%) and 32 (26.3%) of trimethoprim resistant isolates collected in Nigeria in 2005 and 2009, respectively. Additionally, 37 (19.3%) of trimethoprim-resistant E. coli isolates collected between 2006 and 2008 from Ghana were positive for the dfrA7 and a transposon marker, but only 4 (2.1%) harbored the plasmid backbone. Conclusions: Our data point to transposition as a principal mechanism for disseminating dfrA7 among E. coli from Nigeria and Ghana. On-going intensive use of the affordable broad-spectrum antibacterials is likely to promote selective success of a highly prevalent transposable element in West Africa.